Cytometry part A - Darzynkiewicz, Zbigniew; Crissman, Harry A.; Robinson, J. Paul (Methods in cell biology; volume 63, 2001)
Each chapter presents a detailed background of the described method, its theoretical foundations, and its applicability to different biomedical material. Updated chapters describe either the most popular methods or those processes that have evolved the most since the past edition. Additionally, a large portion of the volume is devoted to clinical cytometry. Particular attention is paid to applications of cytometry in oncology, the most rapidly growing area.--Provided by publisher.